IMPLEMENTASI WEB ENGINEERING METHOD PENGELOLAAN PENDISTRIBUSIAN OBAT GUDANG FARMASI DINAS KESEHATAN PAGAR ALAM - Inda Anggraini; Debi Gusmaliza (JUSIM (Jurnal Sistem Informasi Musirawas), 2021)
This study aims to design and implement a web-based drug distribution management that can help pharmacy warehouse employees manage drug data and also facilitate the preparation of drug distribution reports. Based on the results of observations and interviews at the pharmacy warehouse, data management is still done manually and has weaknesses, including the problem of ease, speed and accuracy. Management is still done using the Microsoft Office word and excel applications. The system development method used in designing drug distribution management is the Web Engineering method (Customer Communication, Planning, Modeling, Construction, Deployment). Meanwhile, the supporting tools or applications used to design and implement the management of drug distribution are Axure and UML (Unified Modeling Language). The programming language uses HTML, PHP, MySQL database and Farmework codeigniter and system testing uses the Blackbox Testing method with valid or not valid test results. The results of this study are a drug distribution management system at the pharmacy warehouse of the Pagar Alam City Health Service so that it can be used by pharmacy warehouse officers and 7 Puskesmas.